Pelestarian Hutan dan Air dalam Filosofi Kearifan Lokal Desa Tenganan Pagringsingan Karangasem - Dewa Gede Prananta; I Made Pageh; I Wayan Kertih (Universitas Hamzanwadi, 2026)
This study aims to determine the form of local wisdom of Tenganan Pagringsingan Village in the preservation of village forests and water sources. This research is a qualitative descriptive study by conducting observations and interviews with several village community leaders, village heads, traditional heads, and the community. The results of the study show that the people of Tenganan Pagringsingan Village strongly uphold and uphold the existing local wisdom, especially in the form of rituals, myths, and rules. This local wisdom plays a role in maintaining the sustainability of village forests and water sources. These rituals are in the form of Tumpek Wariga and Metruna Nyoman. The Tumpek Wariga ritual is a symbol as a form of gratitude to nature in the mystical sense for the gift of plant fertility so that the community can use it for survival. The Metruna Nyoman ritual, as a form of non-formal education, shapes the character of the younger generation to know their own village, existing rituals, and most importantly, love and protect the environment. The myth that has existed since ancient times is Lelipi Selahan Bukit, a form of belief in forest guardians, so that the community does not dare to do things that cause forest damage. The rules, in the form of customary village regulations, outline the rights and obligations of indigenous communities, along with the accompanying sanctions. These regulations will serve as a binding force for all forms of community behavior, ensuring they conform to the established guidelines.